2017
DOI: 10.21091/mppa.2017.4035
|View full text |Cite
|
Sign up to set email alerts
|

Phonomicrosurgery in Vocal Fold Nodules: Quantification of Outcomes in Professional and Non-Professional Voice Users

Abstract: These results confirm that phonomicrosurgery for VFN is a safe therapy for voice improvement in both PVU and NVU who do not respond to voice therapy alone. Top-level artistic capabilities in PVU were restored, but numeric changes of most vocal parameters were considerably larger in NVU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 0 publications
6
15
0
Order By: Relevance
“…The recently introduced parameter, VEM, demonstrated significant changes with phonosurgery, logopedic treatment and vocal pedagogy in all singers. This confirmed the results of previous studies where the VEM proved to be a comprehensible and easy-to-use measure for objective evaluation of the VRP [19,45]. The standardized VRP and the data thereby determined in order to calculate the DSI are core elements in objective voice diagnostics [67].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The recently introduced parameter, VEM, demonstrated significant changes with phonosurgery, logopedic treatment and vocal pedagogy in all singers. This confirmed the results of previous studies where the VEM proved to be a comprehensible and easy-to-use measure for objective evaluation of the VRP [19,45]. The standardized VRP and the data thereby determined in order to calculate the DSI are core elements in objective voice diagnostics [67].…”
Section: Discussionsupporting
confidence: 87%
“…In organic dysphonia, our study showed that conservative therapy might also be helpful in singers with small marginal edema, but seems not to be effective for restitution of other chronic findings such as keratinized vocal fold nodules or persistent contact granuloma. Our phonosurgical treatment indication and results are in line with published research data concluding that phonomicrosurgical resection is an adequate therapy to improve the voice in singers suffering from chronic benign glottal lesions [19,42]. Comparable to the subgroup of operated patients in our investigation, Zeitels et al [40] prospectively studied the outcome in 185 singers and performing artists who underwent phonomicrosurgical excision of different vocal fold lesions.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations